1990
DOI: 10.1128/iai.58.6.1796-1801.1990
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Friend leukemia virus infection on susceptibility to Candida albicans

Abstract: Previous studies have demonstrated that Friend leukemia virus (FLV) induces a profound immunosuppression in susceptible mice. The studies described in this report indicate that mice infected with FLV have an increased susceptibility to subsequent infection with the opportunistic pathogen Candida albicans, as measured by increased numbers of C. albicans CFU in the kidneys of FLV-infected mice relative to uninfected controls. Experiments in which the NB-tropic and N-tropic strains of FLV were used suggest that v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

1992
1992
1999
1999

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…By 4 weeks, only limited numbers of PMNs were recovered from the peritoneal cavity. These results were essentially similar to those reported previously (15) and show that migration of PMNs to an inflammatory site may be impaired by infection with FLV.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…By 4 weeks, only limited numbers of PMNs were recovered from the peritoneal cavity. These results were essentially similar to those reported previously (15) and show that migration of PMNs to an inflammatory site may be impaired by infection with FLV.…”
supporting
confidence: 92%
“…For example, various functions of immunologically important cells, including B and T lymphocytes as well as macrophages, are markedly affected after infection of mice with this virus. A recent study by Moors et al demonstrated that impairment of antimicrobial activity of neutrophils also occurs after FLV infection of susceptible mice (15). That is, immune responses to Candida albicans, a ubiquitous opportunistic fungus which causes infections in immunosuppressed individuals, including those with AIDS (19), are depressed in mice infected with FLV and challenged with C. albicans.…”
mentioning
confidence: 99%
“…COz. C albicans cultured under the above conditions convert from the yeast to the hyphal form in the presence or absence of human serum (26,27). The extent of hyphal growth after 18 h of culture was determined by [3H]glucose uptake assay (26,27) and by MTT assay (28).…”
Section: Methodsmentioning
confidence: 99%
“…[~H]Glucose Uptake Assay. Assay for Candida hyphal growth by uptake of radiohbded glucose has been described in detail elsewhere (26,27). Briefly, after 18 h of growth under the described experimental conditions, medium was removed, wells were washed with sterile distilled water, and 25 #1 of 2,5[3H]glucose (Net-807, sp act 67 Ci/mMol; New England Nuclear, Boston, MA), diluted to 10 #Ci/ml in sterile water, was added to each well.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation